Increasing Polyamine Contents Enhances the Stress Tolerance via Reinforcement of Antioxidative Properties - Seo, So Yeon; Kim, Yu Jung; Park, Ky Young (Frontiers in Plant Science, 2019)
The diamine putrescine and the polyamines (PAs), spermidine (Spd) and spermine (Spm), are ubiquitously occurring polycations associated with several important cellular functions, especially anti-senescence. Numerous studies have reported increased levels of polyamine in plant cells under conditions of abiotic and biotic stress such as drought, high salt concentrations, and pathogen attack. However, the physiological mechanism of elevated polyamine levels in response to abiotic and biotic stresses remains undetermined. Transgenic plants having overexpression of SAMDC cDNA and increased levels of Put (1.4-fold), Spd (2.3-fold) and Spm (1.8-fold) under unstressed conditions, were compared to WT plants in the current study. The most abundant PA in transgenic plants was Spd. Under salt stress conditions, enhancement of endogenous PAs due to overexpression of the SAMDC gene and exogenous treatment with Spd considerably reduces the reactive oxygen species (ROS) accumulation in intra- and extracellular compartments. Conversely, as compared to the WT, polyamine oxidase (PAO) transcription rapidly increases in the S16-S-4 transgenic strain subsequent to salt stress. Furthermore, transcription levels of ROS detoxifying enzymes are elevated in transgenic plants as compared to the WT. Our findings with OxyBlot analysis indicate that up-regulated amounts of endogenous PAs in transgenic tobacco plants show antioxidative effects for protein homeostasis against stress-induced protein oxidation. These results imply that the increased PAs induce transcription of PAOs which oxidize PAs, which in turn trigger signal antioxidative responses resulting to lower the ROS load. Furthermore, total proteins from leaves with exogenously supplemented Spd and Spm up-regulate the chaperone activity. These effects of PAs for antioxidative properties and anti-aggregation of proteins contribute towards maintaining the physiological cellular functions against abiotic stresses. It is suggested that these functions of PAs are beneficial for protein homeostasis during abiotic stresses. Taken together, these results indicate that PA molecules function as anti-senescence regulators through inducing ROS detoxification, antioxidative properties and molecular chaperone activity under stress conditions, thereby providing broad-spectrum tolerance against a variety of stresses.